The Exploring Students' Career Interests In Islamic Banking: Between Knowledge And Religious Values - Mustika, Dama (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2025)
With the increasing awareness of Sharia-based financial services and the growth of the Sharia banking industry, it is important to understand the determinants of career decisions of the younger generation. This study aims to analyze the factors that influence students' career interest in Sharia banking through Sharia banking knowledge and religiosity. This study uses quantitative data with a questionnaire conducted through Google Forms, distributed to students who have completed the Sharia banking course. The population was 110 respondents at STAI Hubbulwathan, and 63 respondents were research samples who filled out the questionnaire online. The results of the study showed that career interest in Sharia banking was greatly influenced by knowledge of Sharia banking with a p-value of 0.006 and the level of religiosity had a significant effect with a p-value of 0.002 on career interest in Sharia banking. The importance of higher education institutions integrating Islamic banking material more deeply into the curriculum, the need for socialization regarding career prospects in Islamic banking, and Islamic principles in economics are important so that students better understand the opportunities in this sector. Providing training programs, seminars, and short courses can also be an alternative to improve students' practical knowledge.